Silver nanoparticles of variable morphology synthesized in aqueous foams as novel templates - Mandal, Sujata; Arumugam, S. K.; Pasricha, R.; Sastry, M. (Bulletin of Materials Science, 2005)
In this paper, we describe the synthesis of silver nanocrystals within aqueous foams as a template More specifically, we show that aqueous Ag+ ions may be electrostatically complexed with the anionic surfactants aerosol OT (sodium bis-2-ethylhexyl-sulfosuccinate, (AOT) and sodium dodecyl sulphate (SDS)) in a highly stable liquid foam. After drainage of the foam, the silver ions are reduced in situ by introducing sodium borohydride into the foam by capillary flow. This leads to the formation of silver nanoparticles of spherical, tape- and sheet-like morphology in the foam. The structure of the foam is extremely complex and presents reaction sites of different spatial extent. The differences in foam reaction-site geometry are believed to be responsible for the morphology variation in the silver nanoparticles observed. The silver nanoparticles are observed to be extremely stable in solution suggesting that the AOT or SDS molecules stabilize them. This approach appears promising for application in large-scale synthesis of nanoparticles and may be readily extended to other chemical compositions.
Keywords: Chemical synthesis; composites; foam; Intercalation; Nanoparticles

Synthesis and analysis of ZnO and CdSe nanoparticles - Ashtaputre, S. S.; Deshpande, Aparna; Marathe, Sayali; Wankhede, M. E.; Chimanpure, J.; Pasricha, R.; Urban, J.; Haram, Santosh K.; Gosavi, S. W.; Kulkarni, S. K. (Pramana-Journal of Physics, 2005)
Zinc oxide and cadmium selenide particles in the nanometer size regime have been synthesized using chemical routes. The particles were capped using thioglycerol in case of ZnO and 2-mercaptoethanol in case of CdSe to achieve the stability and avoid the coalescence. Zinc oxide nanoparticles were doped with europium to study their optical properties. A variety of techniques like UV-Vis absorption spectroscopy, X-ray diffraction (XRD), photoluminescence (PL), X-ray photoelectron spectroscopy (XPS), Fourier transform infrared spectroscopy (FT-IR) and transmission electron microscopy (TEM) were used to carry out structural and spectroscopic characterizations of the nanoparticles.
Keywords: chemical capping; Doping; Nanoparticles; photoluminescence

Synthesis of bismuth oxide nanoparticles by citrate gel method - Anilkumar, Mettu; Pasricha, R.; Ravi, V. (Ceramics International, 2005)
A mixture of bismuth nitrate and citric acid solution is taken in 1: 1 molar ratio and heated on hot water bath. A gel is formed on evaporation of the water, which on decomposition at 400 degrees C produces nanocrystalline Bi2O3 particles. Formation of nanocrystallites of Bi2O3 is confirmed by X-ray diffraction (XRD) study. Transmission electron microscope (TEM) investigations revealed that the average particle size is 50 nm for these powders. (c) 2004 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: Electron microscopy; powders : chemical preparation; X-ray methods

Synthesis of bismuth oxide nanoparticles using bismuth nitrate and urea - Jha, Ratnesh Kumar; Pasricha, R.; Ravi, V. (Ceramics International, 2005)
A mixture of bismuth nitrate and urea is taken in 1:5 molar ratio and heated on hot water bath. A precipitate is formed on evaporation of the water which on decomposition at 400 degrees C produces nanocrystalline Bi2O3 particles. Formation of nano crystallites of Bi2O3 is confirmed by X-ray diffraction (XRD) study. Transmission electron microscopy (TEM) investigations revealed for these powders an average particle size of 50 nm. (c) 2004 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: calcination; Electron microscopy; X-ray methods

Synthesis of fine particles of ZnO at 100 degrees C - Dhage, S. R.; Pasricha, R.; Ravi, V. (Materials Letters, 2005)
A simple gel to crystal conversion route has been followed for the preparation of fine ZnO at 80-100 degreesC under refluxing conditions. Freshly prepared zinc hydroxide gel is allowed to crystallize under refluxing and stirring conditions for 4-6 It. Formation of fine crystallites of ZnO is confirmed by X-ray diffraction (XRD) study. Transmission electron microscope (TEM) investigations revealed that the average particle size is 100 nm for these powders. (C) 2004 Elsevier B.V All rights reserved.
Keywords: Ceramics; Chemical synthesis; Electron microscopy; Oxides; X-ray diffraction

Synthesis of Sr0.5Ba0.5Nb2O6 by urea method - Dhage, S. R.; Pasricha, R.; Ravi, V. (Materials Letters, 2005)
A precipitate was formed when an aqueous solution of SrCl2, BaCl2, NbF5 and urea in stoichiometric ratio (total metal cations to urea ratio is 5) is heated on a water bath.. This precipitate on decomposition at 750 degreesC yielded the nanocrystallites of ternary oxide, Sr0.5Ba0.5Nb2O6 (SBN) as confirmed by X-ray diffraction study (XRD). This is much lower temperature as compared to that prepared by traditional solid state method (1000 degreesC as reported for the formation of SBN ceramics. Transmission electron microscope (TEM) investigations revealed that the average particle size is 100 nm for the calcined powders. The room temperature dielectric constant at 1 kHz is found to be 1050. The ferroelectric hysteresis loop parameters of these samples were also studied. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: Ceramics; Electron microscopy; ferroelectricity; Oxides